Antibacterial and moisture-proof underwear fabric and preparation method thereof
By using mixed fibers, modified cotton fibers, chitosan and titanium chloride in underwear fabrics, combined with technologies such as blended weaving, ultrasonic spraying, microwave heating and aerogel preparation, the underwear fabrics are solved to absorb moisture in humid environments. and bacterial breeding problems have achieved antibacterial, moisture-proof and breathable effects.
Patent Information
- Application Number
- CN202210185604.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-28
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-02-28
AI Technical Summary
The existing underwear fabric absorbs moisture in a humid environment, affects comfort, and is prone to bacterial growth and affects human health.
70-90 parts of mixed fiber, 70-90 parts of modified cotton fiber, 35-55 parts of chitosan and 21-33 parts of titanium chloride were used to prepare and modify it by blending braiding, ultrasonic spraying, microwave heating, aerogel Prepare antibacterial and moisture-proof underwear fabrics by preparing cotton fiber fabrics.
It achieves antibacterial, moisture-proof and breathable effects, and improves the comfort and health of underwear fabrics.
Smart Images

Figure BDA0003523230170000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textiles, in particular to an antibacterial and moisture-proof underwear fabric and a preparation method thereof. Background Art
[0002] Underwear is one of the most popular clothing types in the textile and clothing market, and is known as the "second skin of the human body." The main functions of underwear are to keep warm, protect the skin, and avoid staining outerwear. However, as far as existing underwear is concerned, most of its functions are often limited to warmth retention. Existing underwear fabrics are often made of cotton fibers and artificial fibers. Due to their own material, they are easy to absorb moisture in the air. In humid environments such as rainy weather, underwear fabrics are easy to absorb moisture, resulting in general comfort when used by users, which often troubles people; at the same time, people wear more clothes in winter, and it is not easy to eliminate sweat in time, which makes the inner layer of underwear fabrics easy to breed bacteria, affecting human health. Based on this, how to prepare an antibacterial, moisture-proof, and breathable underwear fabric is particularly important. Summary of the invention
[0003] The object of the present invention is to provide an antibacterial and moisture-proof underwear fabric and a preparation method thereof, so as to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: an antibacterial and moisture-proof underwear fabric, characterized in that, by weight, it mainly comprises 70 to 90 parts of mixed fibers, 70 to 90 parts of modified cotton fibers, 35 to 55 parts of chitosan, and 21 to 33 parts of titanium chloride.
[0005] Furthermore, the mixed fiber is obtained by blending milk fiber and cotton fiber in a ratio of 2:3 to 3:7; the linear density of the cotton fiber is 1.56 to 1.78 dtex, and the linear density of the milk fiber is 1.33 to 1.44 dtex.
[0006] Furthermore, the modified cotton fiber is prepared by the following method: pretreated cotton fiber, nitric acid, isopropyl ethyl acetate and copper powder are mixed to react to obtain esterified fiber; esterified fiber, benzylmercaptothiocarbonyl propionic acid, azobisisobutyronitrile, dioxane and trioxane are mixed, heated for reaction for a period of time under a nitrogen atmosphere, and then immersed in a chlorohexadecane solution to obtain modified cotton fiber.
[0007] Furthermore, a method for preparing antibacterial and moisture-proof underwear fabric is provided, characterized in that it mainly comprises the following preparation steps: blended weaving, ultrasonic spraying of the mixed liquid, preparation of dendritic titanium dioxide by microwave-assisted electric field heating, preparation of chitosan aerogel, preparation of modified cotton fiber fabric, and pressure-sensitive adhesive bonding.
[0008] Furthermore, the preparation method of the antibacterial and moisture-proof underwear fabric comprises the following preparation steps:
[0009] (1) The mixed fiber is used as warp and weft, and a fabric is woven into a fabric according to a 2 / 2 twill weave using a weaving machine, and then ultrasonically sprayed for 10 to 15 minutes to obtain a fabric base;
[0010] (2) placing the fabric substrate in a microwave synthesis reactor, applying an electric field, heating to 80-90°C in a nitrogen atmosphere, reacting for 50-60 minutes, and obtaining a titanium dioxide fabric; mixing the titanium dioxide fabric and chitosan gel solution in a mass ratio of 1:2-1:3, stirring at 100-200 rpm for 30-40 minutes, placing in a refrigerator, freezing at 0-4°C for 1-2 hours, and then placing in a vacuum freeze dryer, freezing at -45--30°C and 10-15 Pa for 12-14 hours, and irradiating for 4-9 minutes, with an irradiation dose of 100-200 kGy, to obtain an aerogel fabric;
[0011] (3) adding pretreated cotton fiber, nitric acid, isopropyl ethyl acetate and copper powder into a container in a mass ratio of 1:3:0.7:0.05 to 1:5:0.9:0.05, wherein the mass fraction of the nitric acid aqueous solution is 68% and the volume ratio of nitric acid and deionized water is 1:10 to 1:19, reacting at 45 to 55° C. for 5 to 6 hours under a nitrogen atmosphere, removing the fiber, rinsing it with deionized water for 4 to 7 minutes, and drying it at 70 to 80° C. for 5 to 7 minutes to obtain esterified fiber;
[0012] (4) Add esterified fiber, benzylthiocarboxylic acid, azobisisobutyronitrile, dioxane and trioxane in a mass ratio of 1:0.1:0.0005:1:0.002-1:0.3:0.0007:2:0.004 into a reaction bottle, stir at 75-80°C and 200-300 rpm under nitrogen atmosphere for 7-12 h, place in ice water, add dioxane in an amount of 0.2-0.5 times the mass of the esterified fiber, stir at 50-100 rpm for 8-12 h. 16min, add petroleum ether 2 to 4 times the mass of the esterified fiber, let it stand for 17 to 25min, filter, soak in a chlorohexadecane solution 2 to 3 times the mass of the esterified fiber, the mass ratio of chlorohexadecane to isopropanol in the chlorohexadecane solution is 1:10, react at 80 to 85°C for 7 to 8h, filter, wash with 80% ethanol and anhydrous ethanol for 3 to 5 times respectively, and dry at 65 to 70°C and 0.01 to 0.03MPa for 5 to 7h to obtain modified cotton fiber;
[0013] (5) The modified cotton fiber is used as warp and weft, and a 2 / 2 twill weave is used to weave a fabric. The fabric is laminated with an aerogel fabric on a pressure-sensitive adhesive coating machine at a machine speed of 60 to 70 m / min to obtain an antibacterial and moisture-proof underwear fabric.
[0014] Furthermore, in the weaving process of steps (1) (5), the warp density is 40 to 50 strands / cm, and the weft density is 25 to 30 strands / cm.
[0015] Furthermore, the carrier gas for ultrasonic atomization spraying in step (1) is argon gas, and the argon gas flow rate is 1.5 to 2.5 m / s. 3 / h, the spraying liquid is titanium chloride, deionized water and sodium bicarbonate in a mass ratio of 1:6:2.9 to 1:6:3.4, the liquid supply volume is 1 to 4 mL / min, and the spraying height is 10 to 25 mm.
[0016] Furthermore, the microwave power of the microwave synthesis reactor in step (2) is 500-600W; the voltage of the electric field is 300-400V.
[0017] Furthermore, the preparation method of the chitosan gel solution in step (2) is as follows: chitosan and acetic acid with a mass fraction of 2.5% are added into a container at a mass ratio of 1:8 to 1:10, and stirred at 500 to 600 rpm for 15 to 22 minutes, and then glutaraldehyde with a mass fraction of 4.6 to 5.3 times that of the chitosan and Span-80 with a mass fraction of 0.08 to 0.1 times that of the chitosan are added, and the chitosan gel solution is obtained by stirring at the same speed for 7 to 12 minutes.
[0018] Furthermore, the preparation method of the pretreated cotton fiber in step (3) is: completely immersing the cotton fiber in an ammonium cerium nitrate solution, wherein the mass ratio of ammonium cerium nitrate to deionized water is 1:91, immersing the cotton fiber at 25-30° C. for 2-3 hours, then taking it out and rinsing it with deionized water for 5-7 minutes.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0020] The underwear fabric of the present invention is prepared through the steps of blended weaving, ultrasonic spraying of mixed liquid, preparation of dendritic titanium dioxide, preparation of aerogel, preparation of modified cotton fiber fabric, pressure-sensitive adhesive bonding, etc., and has achieved the effects of antibacterial, moisture-proof and breathable.
[0021] Firstly, cotton fiber and milk fiber are blended and woven into a fabric base to form a skin-friendly fabric layer, and then a mixture of titanium chloride and sodium bicarbonate is sprayed using ultrasonic atomization. The chloride ions of titanium chloride react with the hydroxyl groups on the surface of the cotton fiber and firmly adhere to the fiber. Then, low-temperature microwave-assisted electric field heating of the fabric base forms dendritic titanium dioxide on the surface, making the underwear fabric antibacterial. The thermal effect and non-thermal effect of microwaves cause an instantaneous rapid temperature rise to generate a large number of titanium dioxide crystal nuclei, and the introduction of an external electric field accelerates the diffusion of atoms on the surface of the crystal nucleus, gradually generating a dendritic structure. At the same time, microwave combined with electric field heating can prepare titanium dioxide at low temperature and normal pressure, avoiding damage to the fabric base by high temperature. In addition, titanium dioxide released by the reaction of titanium chloride and sodium bicarbonate Carbon dioxide and hydrogen are used to make the surface and interior of the dendritic structure present pores, making the fabric breathable; then, dendritic titanium dioxide is used as the skeleton and chitosan aerogel is prepared by vacuum freeze drying. Chitosan penetrates into the interior of titanium dioxide from the pores on the surface of titanium dioxide and reacts with the hydroxyl groups on the surface of titanium dioxide to form covalent cross-links. Thus, the chitosan aerogel and titanium dioxide form a three-dimensional network cross-linked structure. The pores of the aerogel are connected with the pores of titanium dioxide, which improves the air permeability of the fabric. At the same time, the chitosan aerogel protects the titanium dioxide from external forces. The surface chitosan aerogel is then irradiated to improve the antibacterial property of the fabric; finally, the modified cotton fiber is spun to obtain the fabric, which is adhered to the surface of the aerogel using pressure-sensitive adhesive bonding technology to obtain underwear fabric.
[0022] Secondly, the modified cotton fiber is prepared from cotton fiber, isopropylene ethyl acetate, benzylmercaptothiocarbonyl propionic acid and hexadecane chloride; the hydroxyl group on the surface of the cotton fiber reacts with the ester group of isopropylene ethyl acetate to graft isopropylene ethyl acetate onto the surface of the cotton fiber, and under the action of an initiator, the thiocarbonyl group of benzylmercaptothiocarbonyl propionic acid and the propenyl group of isopropylene acetate polymerize to form a hydrophobic film on the fiber surface, so that the underwear fabric has waterproof and moisture-proof properties; then the carboxyl group of benzylmercaptothiocarbonyl propionic acid reacts with the chloride ion of hexadecane chloride, and the long-chain alkyl group is entangled on the surface of the cotton fiber, thereby reducing the surface free energy of the modified cotton fiber and improving the moisture-proof property of the underwear fabric. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the test methods of various indicators of the antibacterial and moisture-proof underwear fabrics prepared in the following examples are as follows:
[0025] Antibacterial property: The antibacterial effect of the embodiment and the comparative example of the same size was tested according to GB / T 20944.3 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method".
[0026] Moisture resistance: Take the same size of the embodiment and the comparative example to test the moisture resistance effect, refer to GB / T 9995 "Determination of moisture content and moisture regain of textile materials".
[0027] Air permeability: The air permeability of the embodiments and comparative examples of the same size was tested according to GB / T5453 “Determination of Air Permeability of Textile Fabrics”.
[0028] Example 1
[0029] An antibacterial and moisture-proof underwear fabric mainly comprises, by weight, 70 parts of mixed fibers, 70 parts of modified cotton fibers, 35 parts of chitosan, and 21 parts of titanium chloride.
[0030] A method for preparing an antibacterial and moisture-proof underwear fabric, the method for preparing the antibacterial and moisture-proof underwear fabric mainly comprises the following preparation steps:
[0031] (1) Milk fiber and cotton fiber are blended in a ratio of 2:3 to obtain a mixed fiber, wherein the cotton fiber linear density is 1.56 dtex and the milk fiber linear density is 1.33 dtex; the mixed fiber is used as warp and weft, wherein the warp density is 40 strands / cm and the weft density is 25 strands / cm, and the mixed fiber is woven into a fabric in a 2 / 2 twill weave using a weaving machine, and then ultrasonically sprayed for 10 minutes to obtain a fabric base; the carrier gas for the ultrasonic atomization spraying is argon, and the argon flow rate is 2.5 m 3 / h, the spraying liquid is titanium chloride, deionized water and sodium bicarbonate in a mass ratio of 1:6:2.9, the liquid supply is 4mL / min, and the spraying height is 10mm;
[0032] (2) Place the fabric substrate in a 500W microwave synthesis reactor, apply an electric field with a voltage of 300V, heat to 80°C in a nitrogen atmosphere, react for 60min, and obtain titanium dioxide fabric; add chitosan and acetic acid with a mass fraction of 2.5% into the container in a mass ratio of 1:8, stir at 500rpm for 22min, add glutaraldehyde with a mass fraction of 4.6 times that of chitosan and Span-80 with a mass fraction of 0.08 times that of chitosan, and stir at the same speed for 12min to obtain chitosan gel solution; mix the titanium dioxide fabric and chitosan gel solution in a mass ratio of 1:2, stir at 100rpm for 40min, place in a refrigerator, freeze at 0°C for 1h, and then place in a vacuum freeze dryer, freeze at -45°C and 15Pa for 12h, irradiate for 4min, and the irradiation dose is 200kGy to obtain aerogel fabric;
[0033] (3) The cotton fiber is completely immersed in an ammonium cerium nitrate solution, wherein the mass ratio of ammonium cerium nitrate to deionized water is 1:91, and after soaking at 25°C for 3 hours, the cotton fiber is removed and rinsed with deionized water for 5 minutes to obtain the pretreated fiber; the pretreated cotton fiber, nitric acid, ethyl acetate and copper powder are added to a container at a mass ratio of 1:3:0.7:0.05, the mass fraction of the nitric acid aqueous solution is 68%, and the volume ratio of nitric acid to deionized water is 1:10, and the reaction is carried out at 45°C under a nitrogen atmosphere for 6 hours, and then the fiber is removed, rinsed with deionized water for 4 minutes, and dried at 70°C for 7 minutes to obtain the esterified fiber;
[0034] (4) Add esterified fiber, benzylthiothiocarbonyl propionic acid, azobisisobutyronitrile, dioxane and trioxane in a mass ratio of 1:0.1:0.0005:1:0.002 to a reaction bottle, stir and react at 75°C and 200 rpm for 12 hours under a nitrogen atmosphere, place in ice water, add dioxane 0.2 times the mass of the esterified fiber, stir at 50 rpm for 16 minutes, add petroleum ether 2 times the mass of the esterified fiber, let stand for 17 minutes, filter, soak in a chlorohexadecane solution 2 times the mass of the esterified fiber, the mass ratio of chlorohexadecane to isopropanol in the chlorohexadecane solution is 1:10, react at 80°C for 7 hours, filter, wash with 80% ethanol and anhydrous ethanol three times, respectively, and dry at 65°C and 0.03 MPa for 7 hours to obtain modified cotton fiber;
[0035] (5) The modified cotton fiber is used as the warp and weft with a linear density of 40 strands / cm and a weft density of 25 strands / cm. The fabric is woven into a fabric according to a 2 / 2 twill weave using a weaving machine. The fabric is laminated with an aerogel fabric on a pressure-sensitive adhesive coating machine at a machine speed of 60 m / min to obtain an antibacterial and moisture-proof underwear fabric.
[0036] Example 2
[0037] An antibacterial and moisture-proof underwear fabric mainly comprises, by weight, 80 parts of mixed fibers, 80 parts of modified cotton fibers, 45 parts of chitosan, and 27 parts of titanium chloride.
[0038] A method for preparing an antibacterial and moisture-proof underwear fabric, the method for preparing the antibacterial and moisture-proof underwear fabric mainly comprises the following preparation steps:
[0039] (1) Milk fiber and cotton fiber are blended in a ratio of 2:5 to obtain a mixed fiber, wherein the cotton fiber linear density is 1.67 dtex and the milk fiber linear density is 1.39 dtex; the mixed fiber is used as warp and weft, wherein the warp density is 45 strands / cm and the weft density is 28 strands / cm; the mixed fiber is woven into a fabric in a 2 / 2 twill weave using a weaving machine, and then ultrasonically sprayed for 13 minutes to obtain a fabric base; the carrier gas for the ultrasonic spraying is argon, and the argon flow rate is 2.0 m 3 / h, the spraying liquid is titanium chloride, deionized water and sodium bicarbonate in a mass ratio of 1:6:3.15, the liquid supply is 2.5mL / min, and the spraying height is 18mm;
[0040] (2) Place the fabric substrate in a 550W microwave synthesis reactor, apply an electric field with a voltage of 350V, heat to 85°C in a nitrogen atmosphere, react for 55 minutes, and obtain titanium dioxide fabric; add chitosan and acetic acid with a mass fraction of 2.5% into the container in a mass ratio of 1:9, stir at 550rpm for 19 minutes, add glutaraldehyde with a mass fraction of 4.95 times that of chitosan and Span-80 with a mass fraction of 0.09 times that of chitosan, and stir at the same speed for 9 minutes to obtain chitosan gel liquid; mix the titanium dioxide fabric and chitosan gel liquid in a mass ratio of 1:2.5, stir at 150rpm for 35 minutes, place in a refrigerator, freeze at 2°C for 1.5 hours, and then put into a vacuum freeze dryer, freeze at -38°C and 13Pa for 13 hours, irradiate for 6 minutes, and the irradiation dose is 150kGy to obtain aerogel fabric;
[0041] (3) The cotton fiber is completely immersed in an ammonium cerium nitrate solution, wherein the mass ratio of ammonium cerium nitrate to deionized water is 1:91, and after soaking at 28°C for 2.5 hours, the cotton fiber is removed and rinsed with deionized water for 6 minutes to obtain the pretreated fiber; the pretreated cotton fiber, nitric acid, ethyl acetate and copper powder are added to a container at a mass ratio of 1:4:0.8:0.05, the mass fraction of the nitric acid aqueous solution is 68%, and the volume ratio of nitric acid to deionized water is 1:14.5, and the reaction is carried out at 50°C under a nitrogen atmosphere for 5.5 hours, and then the fiber is removed, rinsed with deionized water for 6 minutes, and dried at 75°C for 6 minutes to obtain the esterified fiber;
[0042] (4) Add esterified fiber, benzylthiothiocarbonyl propionic acid, azobisisobutyronitrile, dioxane and trioxane in a mass ratio of 1:0.2:0.0006:1.5:0.003 to a reaction bottle, stir and react at 78°C and 250 rpm for 10 hours under a nitrogen atmosphere, place in ice water, add dioxane 0.35 times the mass of the esterified fiber, stir at 75 rpm for 12 minutes, add petroleum ether 3 times the mass of the esterified fiber, let stand for 21 minutes, filter, soak in a chlorohexadecane solution 2.5 times the mass of the esterified fiber, the mass ratio of chlorohexadecane to isopropanol in the chlorohexadecane solution is 1:10, react at 83°C for 7.5 hours, filter, wash with 80% ethanol and anhydrous ethanol 4 times, respectively, and dry at 68°C and 0.02 MPa for 6 hours to obtain modified cotton fiber;
[0043] (5) The modified cotton fiber is used as the warp and weft with a linear density of 45 strands / cm and a weft density of 28 strands / cm. The fabric is woven into a fabric according to a 2 / 2 twill weave using a weaving machine. The fabric is laminated with an aerogel fabric on a pressure-sensitive adhesive coating machine at a machine speed of 65 m / min to obtain an antibacterial and moisture-proof underwear fabric.
[0044] Example 3
[0045] An antibacterial and moisture-proof underwear fabric mainly comprises, by weight, 90 parts of mixed fibers, 90 parts of modified cotton fibers, 55 parts of chitosan, and 33 parts of titanium chloride.
[0046] A method for preparing an antibacterial and moisture-proof underwear fabric, the method for preparing the antibacterial and moisture-proof underwear fabric mainly comprises the following preparation steps:
[0047] (1) Milk fiber and cotton fiber are blended in a ratio of 3:7 to obtain a mixed fiber, wherein the linear density of the cotton fiber is 1.78 dtex and the linear density of the milk fiber is 1.44 dtex; the mixed fiber is used as the warp and weft, wherein the warp density is 50 strands / cm and the weft density is 30 strands / cm, and the mixed fiber is woven into a fabric in a 2 / 2 twill weave using a weaving machine, and then ultrasonically sprayed for 15 minutes to obtain a fabric base; the carrier gas for the ultrasonic atomization spraying is argon, and the argon flow rate is 1.5 m 3 / h, the spraying liquid is titanium chloride, deionized water and sodium bicarbonate in a mass ratio of 1:6:3.4, the liquid supply is 1mL / min, and the spraying height is 10mm;
[0048] (2) Place the fabric substrate in a 600W microwave synthesis reactor, apply an electric field with a voltage of 400V, heat to 90°C in a nitrogen atmosphere, react for 50min, and obtain titanium dioxide fabric; add chitosan and acetic acid with a mass fraction of 2.5% into the container in a mass ratio of 1:10, stir at 600rpm for 15min, add glutaraldehyde with a mass fraction of 5.3 times that of chitosan and Span-80 with a mass fraction of 0.1 times that of chitosan, and stir at the same speed for 7min to obtain chitosan gel liquid; mix the titanium dioxide fabric and chitosan gel liquid in a mass ratio of 1:3, stir at 200rpm for 30min, place in a refrigerator, freeze at 4°C for 2h, and then place in a vacuum freeze dryer, freeze at -30°C and 15Pa for 14h, irradiate for 9min, and the irradiation dose is 100kGy to obtain aerogel fabric;
[0049] (3) The cotton fiber is completely immersed in an ammonium cerium nitrate solution, wherein the mass ratio of ammonium cerium nitrate to deionized water is 1:91, and after soaking at 30°C for 3 hours, the cotton fiber is removed and rinsed with deionized water for 7 minutes to obtain the pretreated fiber; the pretreated cotton fiber, nitric acid, ethyl acetate and copper powder are added to a container at a mass ratio of 1:5:0.9:0.05, the mass fraction of the nitric acid aqueous solution is 68%, and the volume ratio of nitric acid to deionized water is 1:19, and the reaction is carried out at 55°C under a nitrogen atmosphere for 5 hours, and then the fiber is removed, rinsed with deionized water for 7 minutes, and dried at 80°C for 5 minutes to obtain the esterified fiber;
[0050] (4) Add esterified fiber, benzylthiothiocarbonyl propionic acid, azobisisobutyronitrile, dioxane and trioxane in a mass ratio of 1:0.3:0.0007:2:0.004 to a reaction bottle, stir and react at 80°C and 300 rpm for 7 hours under a nitrogen atmosphere, place in ice water, add dioxane 0.5 times the mass of the esterified fiber, stir at 100 rpm for 8 minutes, add petroleum ether 4 times the mass of the esterified fiber, let stand for 25 minutes, filter, soak in a chlorohexadecane solution 3 times the mass of the esterified fiber, the mass ratio of chlorohexadecane to isopropanol in the chlorohexadecane solution is 1:10, react at 85°C for 7 hours, filter, wash with 80% ethanol and anhydrous ethanol 5 times, respectively, and dry at 70°C and 0.03 MPa for 7 hours to obtain modified cotton fiber;
[0051] (5) The modified cotton fiber is used as the warp and weft with a linear density of 50 strands / cm and a weft density of 30 strands / cm. The fabric is woven into a fabric according to a 2 / 2 twill weave using a weaving machine. The fabric is laminated with an aerogel fabric on a pressure-sensitive adhesive coating machine at a machine speed of 70 m / min to obtain an antibacterial and moisture-proof underwear fabric.
[0052] Comparative Example 1
[0053] An antibacterial and moisture-proof underwear fabric mainly comprises, by weight, 80 parts of mixed fibers, 80 parts of cotton fibers, 45 parts of chitosan, and 27 parts of titanium chloride.
[0054] A method for preparing an antibacterial and moisture-proof underwear fabric, the method for preparing the antibacterial and moisture-proof underwear fabric mainly comprises the following preparation steps:
[0055] (1) Milk fiber and cotton fiber are blended in a ratio of 2:5 to obtain a mixed fiber, wherein the cotton fiber linear density is 1.67 dtex and the milk fiber linear density is 1.39 dtex; the mixed fiber is used as warp and weft, wherein the warp density is 45 strands / cm and the weft density is 28 strands / cm; the mixed fiber is woven into a fabric in a 2 / 2 twill weave using a weaving machine, and then ultrasonically sprayed for 13 minutes to obtain a fabric base; the carrier gas for the ultrasonic spraying is argon, and the argon flow rate is 2.0 m 3 / h, the spraying liquid is titanium chloride, deionized water and sodium bicarbonate in a mass ratio of 1:6:3.15, the liquid supply is 2.5mL / min, and the spraying height is 18mm;
[0056] (2) Place the fabric substrate in a 550W microwave synthesis reactor, apply an electric field with a voltage of 350V, heat to 85°C in a nitrogen atmosphere, react for 55 minutes, and obtain titanium dioxide fabric; add chitosan and acetic acid with a mass fraction of 2.5% into the container in a mass ratio of 1:9, stir at 550rpm for 19 minutes, add glutaraldehyde with a mass fraction of 4.95 times that of chitosan and Span-80 with a mass fraction of 0.09 times that of chitosan, and stir at the same speed for 9 minutes to obtain chitosan gel liquid; mix the titanium dioxide fabric and chitosan gel liquid in a mass ratio of 1:2.5, stir at 150rpm for 35 minutes, place in a refrigerator, freeze at 2°C for 1.5 hours, and then put into a vacuum freeze dryer, freeze at -38°C and 13Pa for 13 hours, irradiate for 6 minutes, and the irradiation dose is 150kGy to obtain aerogel fabric;
[0057] (3) Cotton fibers are used as warp and weft with a linear density of 45 strands / cm and a weft density of 28 strands / cm. The fabric is woven into a fabric according to a 2 / 2 twill weave using a weaving machine. The fabric is laminated with an aerogel fabric on a pressure-sensitive adhesive coating machine at a machine speed of 65 m / min to obtain an antibacterial and moisture-proof underwear fabric.
[0058] Comparative Example 2
[0059] The prescription composition of Comparative Example 2 is the same as that of Example 2. The preparation method of the antibacterial and moisture-proof underwear fabric is different from that of Example 2 only in step (2), and step (2) is modified as follows: placing a fabric substrate in a heating furnace, applying an electric field with a voltage of 350 V, heating to 550° C. in a nitrogen atmosphere, and reacting for 75 minutes to obtain a titanium dioxide fabric; adding chitosan and acetic acid with a mass fraction of 2.5% into a container in a mass ratio of 1:9, stirring at 550 rpm for 19 minutes, adding glutaraldehyde with a mass fraction of 4.95 times that of chitosan and Span-80 with a mass fraction of 0.09 times that of chitosan, and stirring at the same speed for 9 minutes to obtain a chitosan gel solution; mixing the titanium dioxide fabric and the chitosan gel solution in a mass ratio of 1:2.5, stirring at 150 rpm for 35 minutes, placing in a refrigerator, freezing at 2° C. for 1.5 hours, and then placing in a vacuum freeze dryer, freezing at -38° C. and 13 Pa for 13 hours, and irradiating for 6 minutes with an irradiation dose of 150 kGy to obtain an aerogel fabric. The remaining preparation steps are the same as in Example 2.
[0060] Comparative Example 3
[0061] The prescription composition of Comparative Example 3 is the same as that of Example 2. The preparation method of the antibacterial and moisture-proof underwear fabric is different from that of Example 2 only in step (2), and step (2) is modified as follows: placing a fabric substrate in a 550W microwave synthesis reactor, heating to 85°C in a nitrogen atmosphere, and reacting for 55 minutes to obtain a titanium dioxide fabric; adding chitosan and acetic acid with a mass fraction of 2.5% into a container in a mass ratio of 1:9, stirring at 550rpm for 19 minutes, adding glutaraldehyde with a mass fraction of 4.95 times that of chitosan and Span-80 with a mass fraction of 0.09 times that of chitosan, and stirring at the same speed for 9 minutes to obtain a chitosan gel solution; mixing the titanium dioxide fabric and the chitosan gel solution in a mass ratio of 1:2.5, stirring at 150rpm for 35 minutes, placing in a refrigerator, freezing at 2°C for 1.5 hours, and then placing in a vacuum freeze dryer, freezing at -38°C and 13Pa for 13 hours, and irradiating for 6 minutes with an irradiation dose of 150kGy to obtain an aerogel fabric. The remaining preparation steps are the same as in Example 2.
[0062] Comparative Example 4
[0063] The prescription composition of comparative example 4 is: 80 parts of mixed fiber, 80 parts of cotton fiber, and 27 parts of titanium chloride. The difference between the preparation method of the antibacterial and moisture-proof underwear fabric and that of Example 2 is only the difference in step (2), which is modified as follows: placing the fabric substrate in a 550W microwave synthesis reactor, applying an electric field with a voltage of 350V, heating to 85°C under a nitrogen atmosphere, and reacting for 55 minutes to obtain a titanium dioxide fabric. The remaining preparation steps are the same as those of Example 2.
[0064] Comparative Example 5
[0065] An antibacterial and moisture-proof underwear fabric mainly comprises, by weight, 80 parts of mixed fibers, 80 parts of cotton fibers, and 27 parts of titanium chloride.
[0066] A method for preparing an antibacterial and moisture-proof underwear fabric, the method for preparing the antibacterial and moisture-proof underwear fabric mainly comprises the following preparation steps:
[0067] (1) Milk fiber and cotton fiber are blended in a ratio of 2:5 to obtain a mixed fiber, wherein the cotton fiber linear density is 1.67 dtex and the milk fiber linear density is 1.39 dtex; the mixed fiber is used as warp and weft, wherein the warp density is 45 strands / cm and the weft density is 28 strands / cm; the mixed fiber is woven into a fabric in a 2 / 2 twill weave using a weaving machine, and then ultrasonically sprayed for 13 minutes to obtain a fabric base; the carrier gas for the ultrasonic spraying is argon, and the argon flow rate is 2.0 m 3 / h, the spraying liquid is titanium chloride, deionized water and sodium bicarbonate in a mass ratio of 1:6:3.15, the liquid supply is 2.5mL / min, and the spraying height is 18mm;
[0068] (2) placing the fabric substrate in a heating furnace, applying an electric field with a voltage of 350 V, heating to 550° C. in a nitrogen atmosphere, and reacting for 65 minutes to obtain a titanium dioxide fabric;
[0069] (3) Cotton fibers are used as warp and weft with a linear density of 45 strands / cm and a weft density of 28 strands / cm. The fabric is woven into a fabric according to a 2 / 2 twill weave using a weaving machine. The fabric is laminated with a titanium dioxide fabric on a pressure-sensitive adhesive coating machine at a machine speed of 65 m / min to obtain an antibacterial and moisture-proof underwear fabric.
[0070] Effect example
[0071] Table 1 below shows the performance analysis results of the antibacterial and moisture-proof underwear fabrics of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0072] Table 1
[0073]
[0074] From the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 5, it can be found that by using modified cotton fibers in the product, a hydrophobic film is formed on the surface of the cotton fibers, so that the underwear fabric has moisture resistance; the fabric base is heated by a low-temperature microwave-assisted electric field to form a porous dendritic titanium dioxide, so that the fabric has antibacterial and breathable properties, and then the titanium dioxide is used as a skeleton to prepare chitosan aerogel, which improves the antibacterial property of the underwear fabric, and the chitosan aerogel and the titanium dioxide pores are interconnected, thereby improving the breathability of the underwear fabric; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 1, it can be found that if the cotton fiber is not modified, the long-chain alkyl cannot be introduced to wrap around the surface of the cotton fiber, and the hydrophobic film cannot be formed, which causes the cotton fiber to be easily hygroscopic. Moisture regain affects the moisture resistance of the underwear fabric; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Examples 2 and 3, it can be found that if low-temperature microwave heating is not used, the microwave thermal effect cannot be utilized for uniform and rapid heating, and a large number of crystal nuclei cannot be generated. At the same time, without the action of an external electric field, it is impossible to rely on the electric field attraction to form a porous dendrite, thereby reducing the antibacterial and air permeability of the underwear fabric; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 4, it can be found that if chitosan aerogel is not generated on the basis of titanium dioxide, titanium dioxide is easily damaged in the subsequent pressure-sensitive bonding process, affecting the antibacterial properties of the underwear fabric. At the same time, the porosity of the titanium dioxide pores is small, and the subsequent damage to the closed pores affects the air permeability of the underwear fabric.
[0075] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. An antibacterial and moisture-proof underwear fabric, characterized in that: The composition comprises 70-90 parts of mixed fiber, 70-90 parts of modified cotton fiber, 35-55 parts of chitosan and 21-33 parts of titanium chloride by weight; The preparation method of the antibacterial and moisture-proof underwear fabric comprises the following preparation steps: (1) The mixed fiber is used as the warp and weft, and the fabric is woven into a 2 / 2 twill fabric using a weaving machine. The fabric is then ultrasonically sprayed for 10 to 15 minutes. The carrier gas for ultrasonic spraying is argon, and the argon flow rate is 1.5 to 2.5 m 3 / h, the spraying liquid is titanium chloride, deionized water and sodium bicarbonate in a mass ratio of 1:6:2.9~1:6:3.4, the liquid supply volume is 1~4mL / min, and the spraying height is 10~25mm to obtain a fabric base; (2) chitosan and acetic acid (mass fraction: 2.5%) were added into a container at a mass ratio of 1:8-1:10, and stirred at 500-600 rpm for 15-22 min. Then, glutaraldehyde (4.6-5.3 times the mass of chitosan) and Span-80 (0.08-0.1 times the mass of chitosan) were added, and stirred at the same speed for 7-12 min to obtain a chitosan gel solution. The fabric substrate is placed in a microwave synthesis reactor, an electric field is applied, the temperature is raised to 80-90°C in a nitrogen atmosphere, and the reaction is performed for 50-60 minutes to obtain a titanium dioxide fabric; the titanium dioxide fabric and the chitosan gel solution are mixed in a mass ratio of 1:2-1:3, stirred at 100-200 rpm for 30-40 minutes, placed in a refrigerator, frozen at 0-4°C for 1-2 hours, and then placed in a vacuum freeze dryer, frozen at -45--30°C and 10-15 Pa for 12-14 hours, and irradiated for 4-9 minutes with an irradiation dose of 100-200 kGy to obtain an aerogel fabric; (3) completely immersing the cotton fiber in a cerium ammonium nitrate solution, wherein the mass ratio of cerium ammonium nitrate to deionized water is 1:91, and immersing the cotton fiber at 25-30° C. for 2-3 hours, then taking the cotton fiber out and rinsing it with deionized water for 5-7 minutes to obtain the pretreated cotton fiber; Pretreated cotton fiber, nitric acid, isopropyl ethyl acetate and copper powder are added into a container in a mass ratio of 1:3:0.7:0.05-1:5:0.9:0.05, the mass fraction of nitric acid aqueous solution is 68%, and the volume ratio of nitric acid and deionized water is 1:10-1:
19. After reacting at 45-55°C for 5-6 hours under a nitrogen atmosphere, the fiber is removed, rinsed with deionized water for 4-7 minutes, and dried at 70-80°C for 5-7 minutes to obtain esterified fiber. (4) Add esterified fiber, benzylthiocarboxylic acid, azobisisobutyronitrile, dioxane and trioxane in a mass ratio of 1:0.1:0.0005:1:0.002~1:0.3:0.0007:2:0.004 into a reaction bottle, stir at 75~80°C and 200~300 rpm under nitrogen atmosphere for 7~12 h, place in ice water, add dioxane (0.2~0.5 times the mass of esterified fiber), stir at 50~100 rpm for 8~12 h. 16min, add petroleum ether 2~4 times the mass of esterified fiber, let stand for 17~25min, filter, soak in chlorohexadecane solution 2~3 times the mass of esterified fiber, the mass ratio of chlorohexadecane to isopropanol in the chlorohexadecane solution is 1:10, react at 80~85℃ for 7~8h, filter, wash with 80% ethanol and anhydrous ethanol for 3~5 times respectively, dry at 65~70℃ and 0.01~0.03MPa for 5~7h to obtain modified cotton fiber; (5) The modified cotton fiber is used as the warp and weft, and a 2 / 2 twill weave is used to weave the fabric. The fabric is then laminated with the aerogel fabric on a pressure-sensitive adhesive coating machine at a speed of 60-70 m / min to obtain an antibacterial and moisture-proof underwear fabric.
2. The antibacterial and moisture-proof underwear fabric according to claim 1, characterized in that: The mixed fiber is obtained by blending milk fiber and cotton fiber in a ratio of 2:3 to 3:7; the linear density of the cotton fiber is 1.56 to 1.78 dtex, and the linear density of the milk fiber is 1.33 to 1.44 dtex.
3. The antibacterial and moisture-proof underwear fabric according to claim 1, characterized in that: In the weaving process of steps (1) (5), the warp density is 40-50 strands / cm, and the weft density is 25-30 strands / cm.
4. The antibacterial and moisture-proof underwear fabric according to claim 1, characterized in that: In step (2), the microwave power of the microwave synthesis reactor is 500-600W; the voltage of the electric field is 300-400V.
Citation Information
Patent Citations
Breathable windproof home textile fabric
CN110524969A
Antibacterial fabric for sofa cushion and production process of antibacterial fabric
CN112853755A